Association of Patient Race With Type of Pelvic Organ Prolapse Surgery Performed and Adverse Events. Issue 10 (October 2021) - Cardenas-Trowers, Olivia O.; Gaskins, Jeremy T.; Francis, Sean L.
Abstract : Objectives: This study aimed to determine if there are differences in (1) surgical procedures performed for pelvic organ prolapse (POP) and (2) rates of adverse events between racial groups. Methods: We conducted a retrospective cohort study of women 18 years and older who underwent POP surgery using the 2005–2015 American College of Surgeons National Surgical Quality Improvement Program database. Race was categorized as Black, White, Hispanic, and other minority. Pelvic organ prolapse procedures were organized into 4 groups: (1) hysterectomy without concurrent POP procedures, (2) vaginal wall repair(s) only without apical suspension, (3) apical suspension with or without vaginal wall repair(s), and (4) obliterative procedures. Patient characteristics and rates of adverse events were noted. A multivariable logistic regression model was used to assess the association between patient race and surgical procedures performed for POP. Results: We identified 48, 005 women who met the inclusion criteria. Most women who underwent POP surgery were White (79.6% [n = 38, 191]). Although only contributing to 4.7% (2, 299) of the cohort, Black women experienced higher complication rates compared with White women (10.7% [246] for Black vs 8.9% [3, 417] for White women, P < 0.01). Hispanic and other minority women were less likely to undergo an apical suspension than White women (adjusted odds ratios [aORs], 0.79 [0.75–0.84] for Hispanic women and 0.78 [0.71–0.86] for other minority women; P < 0.001 for both). Obliterative procedures were more likely to be performed in Black, in Hispanic, and especially in other minority women (aORs, 1.53 [1.20–1.92] for Black, 1.33 [1.12–1.58] for Hispanic, and 3.67 [3.04–4.42] for other minority women; P < 0.001 for all). Conclusions: Racial differences exist among women who undergo POP surgery. Abstract : Racial differences exist among women who undergo pelvic organ prolapse surgery.